Measurement, modelling, and evaluation of computing systems and dependability and fault tolerance : 20th International GI/ITG Conference, MMB 2020, Saarbrücken, Germany, March 16-18, 2020, Proceedings /: 20th International GI/ITG Conference, MMB 2020, Saarbrücken, Germany, March 16-18, 2020, Proceedings. ([2020]) - Unknown
No abstract available